STRATEGI PEMASARAN DIGITAL DAN PENDISTRIBUSIAN BATIK TULIS DI KALANGAN MASYARAKAT: STUDY KASUS DESA GAMEL MELALUI SORUM ASOFA CIREBON - Pratiwi, Rina Ari; Susanti, Susan Santi; Dini, Dini Selasi (Fakultas Ekonomi dan Bisnis, 2024)
In distributing written batik, a batik craftsman in Gamel Village needs to have a digital marketing strategy through Sorum Asofa to develop batik cloth more widely in order to preserve batik culture in Cirebon. After the process of distributing written batik cloth from craftsmen, sorum asofa will be redistributed in the form of more creative products. Sorum Asofa's digital marketing strategy process promotes its products by utilizing social media (online) through applications such as Shopee, TikTok Shop, Lazada, and Tokopedia. Apart from that, Sorum Asofa also promotes its products offline (directly) so that innovation is needed that is in line with current technological developments. this this. Written batik is one of the regional cultural heritages that must be preserved both with more modern and traditional processes, so digital marketing has a very important role in preserving regional culture with more modern innovations among local communities and the manufacturing process is different from stamped batik, and mixed batik.Key words: Marketing, Distribution, Handmade Batik, Sorum Asofa